New drainage and irrigation network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The International Programme for Technological Research in Irrigation and Drainage (IPTRID) network aims to improve the exchange and flow of research results in the field of irrigation and drainage. It has two main functions: to assist developing...